English Language Communication Workshop: Participants' Feedback and Its Pedagogical Implications to ELT Classrooms - Idrus, hairuzila; Md Nordin, Shahrina; Chong, Su Li (Universiti Putra Malaysia Press, 2004)
This paper discusses the experience of its authors who conducted an English Language Communication Workshop for undergraduates studying at a local university. The workshop was carried out for ten days and participated by 53 PETRONAS scholarship holders. The objective of the workshop was to promote oral communication skills amongst these participants and build their confidence in using the English language. The aim of this paper is to present an analysis of the participants’ feedback on the workshop and thus, will shed some light on the pedagogical implications in the teaching of oral communication skills. The kinds of activities carried out during the workshop were role-playing, interviewing, video viewing, lingua hunt, drama, forum, individual and group presentations, and group discussions. Indeed, the analysis of the participants’ feedback indicates that the strength of the workshop lies in its activities. Therefore, this paper will discuss the activities and how these activities could further enhance the participants’ oral communication ability.